2023
DOI: 10.1002/mnfr.202200293
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Kinetic Modeling Predicts Similar In Vivo Relative Potency of Senecionine N‐Oxide for Rat and Human at Realistic Low Exposure Levels

Abstract: Scope This study aims to determine if previously developed physiologically‐based kinetic (PBK) model in rat can be modified for senecionine (SEN) and its N‐oxide (SENO), and be used to investigate potential species differences between rat and human in relative potency (REP) of the N‐oxide relative to the parent pyrrolizidine alkaloid (PA). Methods and results In vitro derived kinetic parameters including the apparent maximum velocities (Vmax) and Michaelis–Menten constants (Km) for SENO reduction and SEN clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…It was observed that the PBK-model-based predicted REP PANO to PA values for riddelliine N -oxide 36 and senecionine N -oxide 37 in rats, calculated based on plasma AUC PA levels (method 1), are close to in vivo -derived REP PANO to PA values ( Fig. 7 ) 36 , 37 . Although the kinetic constants for PANO reduction and PA clearance in rats and humans were different, the two REP PANO to PA values at low dose levels were found to be similar for both species 37 .…”
Section: Relative Potency Factors Of Pa N -Oxides At ...mentioning
confidence: 66%
See 4 more Smart Citations
“…It was observed that the PBK-model-based predicted REP PANO to PA values for riddelliine N -oxide 36 and senecionine N -oxide 37 in rats, calculated based on plasma AUC PA levels (method 1), are close to in vivo -derived REP PANO to PA values ( Fig. 7 ) 36 , 37 . Although the kinetic constants for PANO reduction and PA clearance in rats and humans were different, the two REP PANO to PA values at low dose levels were found to be similar for both species 37 .…”
Section: Relative Potency Factors Of Pa N -Oxides At ...mentioning
confidence: 66%
“…It was observed that the PBK-model-based predicted REP PANO to PA values for riddelliine N-oxide [36] and senecionine N-oxide [37] in rats, calculated based on plasma AUC PA levels (method 1), are close to in vivo-derived REP PANO to PA values (▶ Fig. 7) [36,37].…”
Section: Assessment Of the Genotoxic Potency Of Pa N-oxides: Role Of ...mentioning
confidence: 70%
See 3 more Smart Citations